Early warning score in predicting the severity of acute pancreatitis - Poudyal, S; Singh, YP (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Acute Pancreatitisis leading causes of morbidity and mortality worldwide. A third of patientsdevelop severe pancreatitis with progressive organ dysfunction caused by systemic inflammatory response syndrome.Early identification of severe pancreatitis is essential for proper care and preventing complications. Various scoring systems have been developed to determine the severity.An ideal prognostic marker would be that is easily measurable, reproducible and cost effective. Early Warning Score is a simple physiological scoring system that can be reliably measured at the patient’s bedside. This study was aimed to determine the relationship between early warning score and severity of pancreatitis.Methods: Patients admitted with diagnosis of acute pancreatitis were included. Early warning score was calculated four hourly for 72 hours. Modified Marshall Score was determined at admission and at 48 hours. Severity of acute pancreatitis as defined by revised Atlanta Classification. EWS was correlated with severity of AP. EWS≥3 for more than 48 hours were regarded as severe pancreatitis and EWS≥3 at any time was regarded as a predictor of severe pancreatitis.Results: Eighty-six patients were included with 24 (27.9%) with severe pancreatitis. The sensitivity, specificity,positive andnegative predictive valueof EWS≥3 persistent for 48 hours or more in predicting severity were 87.5%, 98.38%, 95.45% and 95.31% respectively. Correlation between EWS and severity of pancreatitis was statistically significant.Conclusion: EWS is useful as an easy and reliable prognostic marker of the evolution and complications of acute pancreatitis.Journal of Society of Surgeons of Nepal Vol.17(1) 2014: 16-20